2004
DOI: 10.1111/j.1365-3164.2004.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitrometabolism of dehydroepiandrosterone and testosterone by canine hair follicle cells

Abstract: The metabolism of radioactive dehydroepiandrosterone (DHEA) and testosterone was studied in dermal papilla cells (DPC) and dermal fibroblasts (DFB) derived from hair follicles from two different body sites (head, flank) of four male, castrated beagle dogs. Thin layer chromatography was used for separation, and autoradiography for identification of the radioactive metabolites. DHEA was metabolized mainly to 11 alpha-OH-testosterone and only to a minor extent to 11 alpha-OH-androstenedione and another unidentifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…Unlabelled steroid standards were visualized via sulfuric acid and heating, as described by Bamberg et al Bamberg et al (2004). The spots were marked by applying radioactivity on the established elution positions afterwards, to enable detection via the beta-imager.…”
Section: Methodsmentioning
confidence: 99%
“…Unlabelled steroid standards were visualized via sulfuric acid and heating, as described by Bamberg et al Bamberg et al (2004). The spots were marked by applying radioactivity on the established elution positions afterwards, to enable detection via the beta-imager.…”
Section: Methodsmentioning
confidence: 99%
“…15) Therefore, several ef-forts to explain the pathogenetic mechanism of AGA had been made in hair epithelial cells as well as DPC. 17,18,[21][22][23] Previous reports showed that the DHT and T treatment elicited an increase in the steady state concentration of a1(I)-procollagen mRNA in human osteoblast-like osteosarcoma cells 24) and that collagen synthesis was stimulated by DFs were exposed to T (10 Ϫ8 M) in the presence or absence of a neutralizing Ab to TGF-b1 (2, 10 mg/ml). Procollagen expression level was identified by Western blot.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given that the pathogenesis of hair cycle arrest is still unclear, either adrenal gland‐derived hormones or other factors related to the hair follicle behaviour might be involved. Canine hair follicles have been shown to express sex steroid receptors, and their cells were shown to metabolize sex steroids . Human hair follicles have been reported to function both as an estrogen target and as an estrogen source …”
Section: Discussionmentioning
confidence: 99%